Antiproliferative-antimicrobial properties and structural analysis of newly synthesized Schiff bases derived from some 1,3,4-thiadiazole compounds - Gür, Mahmut; Yerlikaya, Serife; Şener, Nesrin; Özkınalı, Sevil; Baloglu, Mehmet Cengiz; Gökçe, Halil; Altunoglu, Yasemin Celik; Demir, Serkan; Şener, İzzet (Elsevier BV, 2020)
Abstract The 1,3,4-thiadiazole core has been mainly used as a pharmacological scaffold in medicinal chemistry. A series of Schiff bases derived from 5-substituted-1,3,4-thiadiazole-2-amine were designed and synthesized to investigate their biological activities. Structures of compounds were clarified with FTIR, 1H NMR and elemental analysis. Due to the importance of this core in pharmacology, all these newly synthesized compounds were tested for different biological properties at the same time. Compound 3A ((E)-N-(2,5-dimethoxybenzylidene)-5-(4-methoxyquinolin-2-yl)-1,3,4-thiadiazol-2-amine) and compound 4A ((E)-N-(2,5-dimethoxybenzylidene)-5-(3-methylbenzofuran-2-yl)-1,3,4-thiadiazol-2-amine) possessed high DNA protective ability against oxidative Fenton mixture. Compound 1A ((E)-N-(2,5-dimethoxybenzylidene)-5-(benzo[b]thiophen-2-yl)-1,3,4-thiadiazol-2-amine) and compound 2B ((E)-2-((5-(1H-indol-2-yl)-1,3,4-thiadiazol-2-ylimino)methyl)-6-methoxyphenol) showed strong antimicrobial activity against S. epidermidis. The most effective compound was detected as compound 3A which exhibited cytotoxicity on both PC-3 and MDA-MB-231 cancer cell lines. The IC50 of this compound was calculated as 370.7 μM and 505.1 μM for MDA-MB-231 and PC-3 cells, respectively. Molecular docking studies were also performed to examine the understanding of the mechanism behind the anti-cancer and anti-bacterial properties. For further study, compound 3A has the potential for utilization with chemotherapy drugs to establish a more efficient therapy strategy with minimum cytotoxicity against cancer cells.
Keywords: Breast cancer; Cytotoxic activity; Molecular docking; Antiproliferative agents; Antimicrobial activity; 3. Good health